Targeted Gene Disruption of the Cyclo (L-Phe, L-Pro) Biosynthetic Pathway in Streptomyces sp. US24 Strain. (3rd May 2007) - Sioud, Samiha; Karray-Rebai, Ines; Aouissaoui, Hedi; Aigle, Bertrand; Bejar, Samir; Mellouli, Lotfi
Abstract : We have previously isolated a new actinomycete strain from Tunisian soil called Streptomyces sp. US24, and have shown that it produces two bioactive molecules including a Cyclo (L-Phe, L-Pro) diketopiperazine (DKP). To identify the structural genes responsible for the synthesis of this DKP derivative, a PCR amplification (696 bp) was carried out using the Streptomyces sp. US24 genomic DNA as template and two degenerate oligonucleotides designed by analogy with genes encoding peptide synthetases (NRPS). The detection of DKP derivative biosynthetic pathway of the Streptomyces sp. US24 strain was then achieved by gene disruption via homologous recombination using a suicide vector derived from the conjugative plasmid pSET152 and containing the PCR product. Chromatography analysis, biological tests and spectroscopic studies of supernatant cultures of the wild-type Streptomyces sp. US24 strain and three mutants obtained by this gene targeting disruption approach showed that the amplified DNA fragment is required for Cyclo (L-Phe, L-Pro) biosynthesis in Streptomyces sp. US24 strain. This DKP derivative seems to be produced either directly via a nonribosomal pathway or as a side product in the course of nonribosomal synthesis of a longer peptide.